Generation of human induced pluripotent stem cell line encoding for a genetically encoded voltage indicator Arclight A242 - Rajesh Vivekanandan; Monika Szepes; Maria Elena Ricci Signorini; Denys Kravchenko; Johanna Kiefer; Steffen Berger; Veronika Fricke; Gudrun Göhring; Ina Gruh (Stem Cell Research, 2023)
Genetically encoded voltage indicators (GEVIs) allow for monitoring membrane potential changes in neurons and cardiomyocytes (CMs) as an alternative to patch-clamp techniques. GEVIs facilitate non-invasive, high throughput screening of electrophysiological properties of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). A dual transgenic hiPSC line with Arclight A242 (GEVI) and an antibiotic resistance cardiac selection cassette was successfully generated from an earlier established hiPSC line MHHi001-A. After cardiac differentiation and selection, purified populations of CMs with constitutive GEVI expression can be utilized for studying cardiac development, disease modeling, and drug testing.